FAKTOR-FAKTOR YANG BERPENGARUH PADA PENGASUHAN ANAK - Ela Pebriani; Ranisa Fitriani; Ica Imelia; Rini Purwanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Child parenting is an essential process in shaping children's cognitive, social, emotional, and physical development from an early age. The quality of parenting is influenced by various internal and external factors. This article aims to examine the factors influencing parenting through a literature study. The factors discussed include family socioeconomic conditions, parental education, parenting styles, and social and cultural environments. The results show that socioeconomic conditions and parental education significantly influence parenting quality. Parenting styles also play a direct role in children's emotional and social development. In addition, a supportive social environment contributes to optimizing children's growth and development. Overall, parenting is the result of the interaction of multiple factors that must be considered comprehensively. Therefore, improving parenting literacy and strengthening collaboration between families, schools, and communities are essential to support optimal child development.